Laser powder bed fusion of 3D metamaterials for energy absorption - Wits, W.W.; Vos, C.J. de; Montero Sistiaga, M.L.; Smit, M.J. de (Elsevier, 2025)
Metamaterials with unique energy absorption properties are fabricated by additive manufacturing. Manufacturing limitations, imposed by Laser Powder Bed Fusion (LPBF), hamper the production of in particular 3D metamaterial structures, due to unsupported overhanging struts that are part of the unit cell design. This study analyses two types of 3D metamaterials, the auxetic re-entrant and octet truss. Optimal process parameters are determined experimentally for stainless steel 316L and unit cell design parameters are related to the overall performance of the metamaterial lattices. Drop-weight impact testing experiments are conducted on LPBF-fabricated metamaterial samples. Unique properties for energy absorption, directly related to the metamaterial’s unit cell design, are demonstrated.